Patterns of differentiation in the life history and demography of four recently described species of the Brachionus calyciflorus cryptic species complex. (13th August 2019) - Zhang, Wei; Lemmen, Kimberley D.; Zhou, Libin; Papakostas, Spiros; Declerck, Steven A. J.
Abstract: Brachionus calyciflorus is arguably the most studied freshwater monogonont rotifer. Although it has been recognised as a cryptic species complex for more than a decade, a formal (re‐)description of the four species known so far ( B. calyciflorus, Brachionus dorcas, Brachionus elevatus, and Brachionus fernandoi ) has only recently been made. Information on the ecology of these species is very scant and fragmented. The aim of this study was to test for ecological divergence between these four species, specifically their life history strategy and population demography. We conducted a life history experiment using 12–16 genotypes per species. For each species, genotypes were extracted from at least three different natural populations. In addition, we performed population‐level culture experiments with the aim to compare population growth rates and demographic structure of experimental populations among species. Finally, we searched the literature for life history studies with molecular data allowing retrospective species identification. We found pronounced differences in life history traits between B. fernandoi and the other three species. B. fernandoi had higher egg and juvenile development times and a lower egg production rate and mictic ratio. We detected no significant life history differences among B. calyciflorus, B. elevatus, and B. dorcas . Population growth rates of B. fernandoi and B. calyciflorus were higher than those of B. elevatus and B. dorcas . Life history divergence resulted in marked differences in the demographic structure of populations. Populations of B. fernandoi contained larger fractions of pre‐reproductive females and lower fractions of adult females with sexual eggs than populations of B. calyciflorus, B. elevatus, and B. dorcas . Mortality was found to be highest in B. elevatus and lowest in B. calyciflorus populations. Our results show that a reverse taxonomy approach is powerful in revealing sources of variation in ecologically relevant traits of cryptic species, such as life history and demographic structure. Explicit consideration of this variation is crucial for future studies of their dynamics in natural communities.